Repo man [videorecording (Blu-Ray)] - Stanton, Harry Dean, 1926-2017; Estevez, Emilio, 1962-; Walter, Tracey, 1942- (The Criterion Collection, 2026)
About a weathered repo man in desolate downtown Los Angeles, and the nihilistic middle-class punk he takes under his wing. The job becomes more than either of them bargained for when they get involved in reclaiming a mysterious, and other worldly, Chevy Malibu with a hefty reward attached to it. Featuring the ultimate early-eighties L.A. punk soundtrack, this grungily hilarious odyssey is a politically trenchant take on President Reagan₂s domestic and foreign policy.